Technologies and educational activities for supporting and implementing challenge- based learning - Baloian, Nelson (2006)
Our Challenge-Based Learning (CBL) method can be described as a special form of problem-based learning, in which the problems are of realistic, open-ended nature. Additionally, CBL contains features of experiential and project-based learning approaches. CBL is supported by the provision of Digital Experimentation Toolkits (DExTs) which comprise materials, initial instructions, references to web resources and specific software tools. Technological challenges lie in the ease of use in accessing these data and in communicating the learners' requests and specifications to the remote sites. Within this article we describe several classroom scenarios for the usage of DexTs in schools. Examples are the calculation of the epicenter of an earthquake, the calculation of lunar heights and the definition of strategies for navigation in a maze. The activities described in this paper were conducted within the framework of our COLDEX project (Collaborative Learning and Distributed Experimentation, http://www.coldex.info).